Analisis Shift Share pada Wilayah Terdampak Pandemi di Indonesia - Ade Nurul Aida; Rendy Alvaro (Jurnal Budget : Isu dan Masalah Keuangan Negara, 2021)
This analysis aims to examine what sectors can still be developed so that the economy can improve again. In addition, to determine changes in economic structure in this analysis, shift-share analysis is used. The results of calculations from this shift-share analysis will provide an overview of the elements that can affect changes or shifts in the regional economic structure of Indonesia. Overall, this analysis shows that all sectors in the five provinces (Bali, Riau Islands, Banten, East Kalimantan, and Yogyakarta) have quite varied provincial competitive advantages. In addition, the study results also showed that there was no level of specialization in all sectors in the five provinces. It means that there are no sectors that are centered on certain business activities.